TANGGUNG JAWAB HUKUM PERUSAHAAN PENYEDIA JASA PEMBAYARAN (PJP) TERHADAP PENYALAHGUNAAN KANAL PEMBAYARAN UNTUK TRANSAKSI ILEGAL - Hutagaol, Immanuel Maykael Martono Reinhard; Mau, Hedwig Adianto; Widodo, Gatut Hendro Tri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid development of digital payment systems through Payment Service Provider (PJP) companies has significantly enhanced transaction efficiency; however, it has also created legal issues related to the misuse of payment channels for illegal activities such as money laundering, online fraud, and illegal gambling. The central legal problem concerns the unclear boundaries of legal liability imposed upon PJPs when their payment channels are misused by merchants or users. This research applies the theory of legal certainty and the theory of legal liability to assess the extent to which Indonesian positive law regulates the scope of obligations, fault, and liability of PJPs within the digital payment ecosystem. This study employs normative legal research using statute approach, conceptual approach, analytical approach, and comparative approach. The legal materials consist of primary legal sources including legislation governing payment systems, anti-money laundering, and information technology, as well as secondary legal materials derived from legal doctrines and scholarly writings. Data collection was conducted through library research and analyzed qualitatively using grammatical and systematic interpretation methods. The findings indicate that Indonesian positive law does not yet provide clear and definitive limitations regarding PJP liability, resulting in legal uncertainty and potential over-criminalization. In principle, PJPs cannot be held criminally liable in the absence of intent, gross negligence, or participation in unlawful acts. The liability of PJPs is more appropriately positioned within the administrative and risk-based compliance framework, including the obligation to implement prudential principles, Know Your Customer (KYC), and Anti-Money Laundering and Counter-Terrorism Financing (AML/CFT) measures. Accordingly, more comprehensive regulatory clarification is required to ensure legal certainty, protect the digital payment industry, and strengthen the effectiveness of preventing financial cybercrime